Research on the Issue of Standards for Applying Criminal Law to Case Cyber Defamation - Fan, Zhongshi (Transactions on Social Science, Education and Humanities Research, 2024)
With the development of the Internet, the connection between real society and cyberspace has gradually become closer. While the Internet has brought great convenience to people’s lives, it has also given rise to many new problems, with cyber defamation being a typical issue. However, in the current governance of online defamation, the limitations of traditional defamation regulations have become apparent due to the unique nature of cyberspace. Considering the fundamental principles of freedom of expression and Internet defamation, providing targeted recommendations for addressing the challenges present in China’s current laws on Internet defamation is crucial. Specifically, it is important to clarify the standards of criminal law applicable to Internet defamation offenses, establish clear criteria for intervention in both public and private prosecution of such offenses, and maintain a balance in relationships. To achieve this, continuous improvement of relevant laws and regulations is necessary to address the challenges of the Internet era, protect individuals’ legitimate rights and interests, and maintain order and healthy development in cyberspace.